Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam sebagai Strategi Penguatan Karakter Religius dan Profil Pelajar Pancasila - Fadhilah, Fadhilah; Marzuki, Darlina Nuralisyarifah; Fadriati, Fadriati; Suryana, Ermis (Prodi Pendidikan Keagamaan Islam, 2025)
The implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) is an important effort to strengthen students’ religious character and internalize the values of the Pancasila Student Profile in schools. This study aims to analyze the conceptual foundation and relevance of the Merdeka Curriculum to Islamic education as a means of achieving holistic character development. Using a library research method, data were collected from books, accredited journal articles, and official government documents related to curriculum policy. The findings show that the Merdeka Curriculum emphasizes independent, contextual, and value-based learning that aligns with Islamic educational principles and supports the six dimensions of the Pancasila Student Profile. The study concludes that integrating the Merdeka Curriculum into Islamic Religious Education effectively enhances students’ religious understanding, moral reasoning, and civic values, contributing to the realization of national education goals.